(3*3)+y=xy

Simple and best practice solution for (3*3)+y=xy equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3*3)+y=xy equation:


Simplifying
(3 * 3) + y = xy

Multiply 3 * 3
(9) + y = xy
9 + y = xy

Solving
9 + y = xy

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1xy' to each side of the equation.
9 + -1xy + y = xy + -1xy

Combine like terms: xy + -1xy = 0
9 + -1xy + y = 0

Add '-9' to each side of the equation.
9 + -1xy + -9 + y = 0 + -9

Reorder the terms:
9 + -9 + -1xy + y = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -1xy + y = 0 + -9
-1xy + y = 0 + -9

Combine like terms: 0 + -9 = -9
-1xy + y = -9

Reorder the terms:
9 + -1xy + y = -9 + 9

Combine like terms: -9 + 9 = 0
9 + -1xy + y = 0

The solution to this equation could not be determined.

See similar equations:

| 3y^9-3y^5= | | 20x+2=142 | | -9x+12=48 | | .75(8x-4)+3=.4(5x+10)-1 | | 20x+2=38 | | 2x+1=5+2x | | 6x=(4x+16) | | 5x+3+8x-5=180 | | 4(2y+3+6y)=32y+12 | | 6-3x=3(8-x) | | b^2+24=-11b | | 3x+y=xy | | p^2+2p=35 | | 7x+6y-1=0 | | 71n+1.7=-3n+5773.7 | | 0.3x^2+2y^2-6=0 | | k^2=15+2k | | .3(2b+9)=.6(b+4.5) | | 3-2*(x+3)=x-18 | | m^2=4m+12 | | 5x+3=6x+1 | | 2x+27=4+x | | 1.5-12-3z=-10 | | -1.5+6+9z=3 | | -7z-14=-10z+16 | | 12(4x+6)+x=-26 | | (3x+20)=(5x+50) | | 2x+1=2-1 | | 16p-4=8(2p-3) | | 3(2-x)=3-(3-x) | | 3/8=a+4/5 | | -5x+24=x |

Equations solver categories